Adaptation and growth kinetics study of an Indian isolate of virulent duck enteritis virus in Vero cells. (January 2015) - Aravind, S.; Kamble, Nitin M.; Gaikwad, Satish S.; Shukla, Sanjeev Kumar; Dey, Sohini; Mohan, C. Madhan
Abstract: Duck virus enteritis, also known as duck plague, is a viral infection of ducks caused by duck enteritis virus (DEV). The control of the disease is mainly done by vaccination with chicken embryo adapted live virus that is known to be poorly immunogenic and elicits only partial protection. Further, the embryo propagated vaccine virus pose a threat of harboring other infectious agents. Seeing these limitations, the present study reports for the first time regarding propagation and adaptation of a virulent Indian isolate of duck enteritis virus in Vero cell line. In this study isolation of an outbreak virus from Kerala state was done in chicken embryo fibroblast cell culture (CEF). Then adapted the DEV isolate in the Vero cell line. The characteristic cytopathic effects (CPE) of clumping and fusion of Vero cells were observed starting from the 7th passage onwards. The presence of the virus and its multiplication in Vero cells was confirmed by detection of viral specific DNA and antigen by using polymerase chain reaction (PCR) and indirect immuno fluorescent assay (IIFA), respectively. PCR detection of DEV using self designed primers for US4 (gD) and UL30 (DNA Polymerase) gene has been reported for the in the present study. The kinetics of DEV in Vero cells revealed a maximum infectivity titer of 10 5.6 TCID50 /ml after 48hr of viral infection. Compared to chicken embryo adapted DVE vaccine virus, the Vero cell culture system is free from other infectious agents. So it will be a good candidate for cultivation and propagation of duck enteritis virus vaccine strain. Further research studies are suggested to explore the feasibility of utilizing this Vero cell culture adapted DEV isolate for developing an attenuated vaccine virus against duck virus enteritis. Highlights: This study is the first report of an attempt to do adaptation of duck enteritis virus in cells of non-avian origin. Isolation of a virulent Indian DEV isolate from clinical samples has done using chicken embryo fibroblast culture. The isolated virus adapted to grow in Vero cell culture. The confirmation of virus has done by PCR using virus specific primers (UL 30 and gD). Growth characteristics and kinetics of DEV in Vero cells has elucidated.